Rancang Bangun Sistem Penghitung Jumlah Pengunjung Perpustakaan Menggunakan Metode Haar like Features (Studi Kasus Pada Perpustakaan Universitas Tadulako) - Nugraha, Deny Wiria; Anshori, Yusuf; Candriasih, Ni Kadek (ScientiCO : Computer Science and Informatics Journal, 2018)
Calculating the number of visitor, in a place or room is not easy. In line, it also occurs when we want to count the number of visitors in library. To know whether the number of visitor in library increases or not, the researcher formulated system that was used to count the visitor. It was Haar Like Features method. This method was used to count the number of visitor in library in a day. In this study, Haar Like Features method was implemented to detect human as object. Beacuse of that, it had function as human object ditector and visotor ditector. By using this method, the librarians felt easier when they counted the visitor in a day. They also could calculate whether the number of visitor in library increased or not.